The T-M-O Framework: Strategic innovation across technology, markets, and organization - Ventresca, M; Seidel, V (University of Oxford, 2020)
How to lead on innovation strategy in times marked by complex emerging technologies, dramatic changes in both markets and wider global politics, and changed demands on organizations in every sector to deliver on value creation and value capture? This teaching note provides an overview of integrative framework developed as part of the content of the Oxford Diploma in Strategy & Innovation, Module 2: Innovation Strategy.